Work Practices and Challenges in Pull-Based Development: The Contributor's Perspective - Gousios, Georgios; Storey, Margaret-Anne; Bacchelli, Alberto (Proceedings / International Conference on Software Engineering, 2016)
The pull-based development model is an emerging way of contributing to distributed software projects that is gaining enormous popularity within the open source software (OSS) world. Previous work has examined this model by focusing on projects and their owners-we complement it by examining the work practices of project contributors and the challenges they face.We conducted a survey with 645 top contributors to active OSS projects using the pull-based model on GitHub, the prevalent social coding site. We also analyzed traces extracted from corresponding GitHub repositories. Our research shows that: contributors have a strong interest in maintaining awareness of project status to get inspiration and avoid duplicating work, but they do not actively propagate information; communication within pull requests is reportedly limited to low-level concerns and contributors often use communication channels external to pull requests; challenges are mostly social in nature, with most reporting poor responsiveness from integrators; and the increased transparency of this setting is a confirmed motivation to contribute. Based on these findings, we present recommendations for practitioners to streamline the contribution process and discuss potential future research directions.